La frontera entre lo humano y lo inhumano como problema hermenéutico (2015)
We understand the need to abandon all-encompassing and definitive perceptions of human nature. However, techno-biological and techno-biocratical developments seem to paradoxically require us to propose boundaries for what is human without being able to believe in these boundaries as before. Such a paradox, which operates both in the epistemic expectations of the natural and human sciences and in debate and public opinion in the globalized world, also poses a challenge to philosophy. Why is it necessary to draw this boundary between the human and the non-human? What type of boundary might this be? Is it even possible to draw such a boundary?